A Scoping Review of Interprofessional Collaboration Between Educators and Health Professionals - Lefebvre, Andrea (Université d'Ottawa / University of Ottawa, 2021)
My thesis examines the interprofessional collaboration between school-based educators and health professionals (HPs). Four research questions guided the study: 1) What is the current state of literature on interprofessional collaborations between school-based educators and HPs? 2) Based on the existing literature, how are school-based educators and HPs collaborating interprofessionally? 3) Based on the existing literature, what are the outcome(s) or impact(s) of interprofessional collaborations between school-based educators and HPs? and 4) Based on the current state of the literature, what areas are important to consider for future research on interprofessional collaborations between school-based educators and HPs? It is important for both school-based educators and HPs alike to consider answers to these questions as it can refine and strengthen their current and future practices in an effort to ultimately create a successful working and learning environment for themselves and for their students and patients. Systematic searches of four databases yielded 46 articles for inclusion, data extraction, and analysis. Through a thematic analysis of the literature, I found the following two overarching themes that govern the implementation of interprofessional collaboration: 1) time and 2) funding. In addition to these themes, I extracted two major themes and one minor theme from the literature that can guide current and future interprofessional collaborative practices. These themes included 1) pre-service training whereby a) everyone is involved, b) there is a mutual understanding between and of educators and HPs, c) both educators and HPs feel valued in their positions for their work, d) there is less sophisticated profession-specific jargon which can in turn open further dialogue between both teams of professionals, and e) a journal or frequent log can be kept to track the successes and challenges of and suggestions for the collaborative efforts as well as of student satisfaction; and 2) in-service training whereby a) educators and HPs are able to maintain consistency in their roles and responsibilities as well as for students educationally, and b) provide continued support for all. I discuss methods of how this interprofessional collaboration could be implemented, noting a) proximity (i.e., how closely, in what ways, and how frequently educators and HPs work together) and b) frequent meetings as essential to successful interprofessional collaboration. Finally, a minor theme emerged from the literature with suggestions for current and ongoing implementation of interprofessional collaboration which suggested a) increased and stronger liaison in schools and b) frequent meetings to establish and build upon a foundation that will foster further interprofessional collaboration. This review of the available literature on this topic, especially of the literature empirical in nature, worked to map key concepts, evidence, and main sources of information as well as synthesize a myriad of information (Arksey and O’Malley, 2005), fill a visible gap in the area of interprofessional collaboration among school-based educators and HPs specifically, and provide avenues for further study and practical application.
Keywords: Interprofessional collaboration; Education; Health professionals; Qualitative; Scoping review